FROM THE HISTORY OF ISSUES OF PHILOSOPHICAL INTERPRETATION OF WORLDVIEW - Kholmatov Shahobiddin Jumaboevich (Galaxy International Interdisciplinary Research Journal, 2023)
The article analyzes the concept of worldview, pluralism, its systematic explanation, and the fact that human worldview is based on scientific ideas.